PROFIL KEMAMPUAN PENALARAN MATEMATIKA DAN POTENSI KOGNITIF SISWA MA DALAM MENYELESAIKAN SOAL TES POTENSI SKOLASTIK (TPS) - Hadi, Samsul (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2022)
Mathematical reasoning and cognitive potential are two student competencies assessed in the SNBT 2023 scholastic potential test. Mathematical reasoning is a student's cognitive ability in making decisions based on analysis, justification, problem solving, and evaluation of problem solving strategies based on data/information on problems solved in everyday life. The aim of the study was to obtain a profile picture of the mathematical reasoning abilities and cognitive potential of SMA students in solving TPS SNBT questions in one of the Privat SMA in East Lombok district, NTB. This research is a qualitative research with a case study design. The participants in this study were 24 students of class XII IPA SMAS Lombok Timur consisting of 8 male students and 16 female students in the odd semester of the 2022-2023 academic year. The instruments in this study were tests of mathematical reasoning and cognitive potential, interviews, observations, and documentation studies. Participant taking technique is done by purposive sampling technique. Data collection was carried out using test and non-test data. The results showed that the profile of students' mathematical reasoning ability and cognitive potential was at a high level in solving TPS SNBT questions but still found: (1) students had difficulties in understanding aspects so students could not identify and understand problems, (2) students had difficulties in modeling aspects /representation of situations so that students cannot make mathematical representations of problems, both models and other mathematical sentences, (3) students have difficulty in cognitive/concept aspects so students cannot create or come up with new strategies in solving problems, and (4) students have difficulties in aspects applied so that students are not able to make and carry out strategies and arithmetical operations correctly.